2015
DOI: 10.2109/jcersj2.123.1084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the template ion exchange behaviors of chromium into FSM-16 on the oxidative dehydrogenation of isobutane

Abstract: The template ion exchange of chromium cations into FSM-16 (#16 Folded Sheets Mesoporous Materials) for 247 h resulted in a 2.89 wt % incorporation of those cations into the FSM-16, although only a 0.3 wt % incorporation had previously been reported. The XRD pattern of the resultant solid (Cr-FSM-16) showed that the hexagonal structure characteristic of FSM-16 remained after the 2.89 wt % incorporation of chromium cations. XPS could be used to detect the Cr 3+ and Cr 6+ species on the surface of Cr-FSM-16. A pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
(25 reference statements)
1
7
1
Order By: Relevance
“…In contrast, in the present study, a trade-off relationship was observed between the selectivity for CO and that for C 3 species, probably owing to the suppressed conversion of CO to CO 2 . In the present study, maximum isobutene yields of more than 15% were detected using Cr-SBA-15 (Si/Cr = 100 and 50) during the initial 2.0 and 3.25 h on-stream, respectively, under the standard reaction conditions used in our previous studies (Sugiyama et al, 2013(Sugiyama et al, , 2015Ehiro et al, 2015Ehiro et al, , 2016aEhiro et al, , 2016bEhiro et al, , 2017, in which the maximum isobutene yield was less than 8%. Additional activity testing using Cr-SBA-15 (Si/Cr = 50) also showed enhanced isobutene yields (16.8 and 15.3% after 0.75 and 2.0 h on-stream, respectively), which were comparable to the above yields.…”
Section: Catalytic Activity Of Sba-15 and Cr-sba-15supporting
confidence: 57%
See 3 more Smart Citations
“…In contrast, in the present study, a trade-off relationship was observed between the selectivity for CO and that for C 3 species, probably owing to the suppressed conversion of CO to CO 2 . In the present study, maximum isobutene yields of more than 15% were detected using Cr-SBA-15 (Si/Cr = 100 and 50) during the initial 2.0 and 3.25 h on-stream, respectively, under the standard reaction conditions used in our previous studies (Sugiyama et al, 2013(Sugiyama et al, , 2015Ehiro et al, 2015Ehiro et al, , 2016aEhiro et al, , 2016bEhiro et al, , 2017, in which the maximum isobutene yield was less than 8%. Additional activity testing using Cr-SBA-15 (Si/Cr = 50) also showed enhanced isobutene yields (16.8 and 15.3% after 0.75 and 2.0 h on-stream, respectively), which were comparable to the above yields.…”
Section: Catalytic Activity Of Sba-15 and Cr-sba-15supporting
confidence: 57%
“…With respect to the structural factors, a specific surface area of greater than 1,600 m 2 /g should be a main contributor to enhanced activity. The growth of micropores in Cr-SBA-15 was detected in the present study, but this feature has not been observed in either FSM-16 or MCM-41 when doped with chromium (Sugiyama et al, 2013(Sugiyama et al, , 2015Ehiro et al, 2015Ehiro et al, , 2016aEhiro et al, , 2016bEhiro et al, , 2017. Therefore, this structural factor is unique to Cr-SBA-15 and results in increased activity.…”
Section: Factors Contributing To Enhanced Catalytic Activity Of Cr-sbcontrasting
confidence: 52%
See 2 more Smart Citations
“…Therefore, introduction of the chromium species into various mesoporous silicas and its effect on the ODH of isobutane has remained a research focus in our laboratory, and we found that the catalyst performance was enhanced (Sugiyama et al, 2015). For example, the chromium species was either introduced or impregnated into various mesoporous silica catalysts possessing a uniform hexagonal structure such as FSM-16 (Sugiyama et al, 2013(Sugiyama et al, , 2015Ehiro et al, 2015) and MCM-41 (Ehiro et al, 2016a(Ehiro et al, , 2016b and great improvement in the yield of isobutene was recorded (≈8% at 723 K). Recently, a similar enhancement was observed during the ODH of isobutane using SBA-15 when a trace amount of chromium was introduced (Kato et al, 2018).…”
Section: Introductionmentioning
confidence: 97%